2022
DOI: 10.1186/s10194-022-01526-5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in functional connectivity and pain-induced brain activations in patients with migraine: a functional MRI study pre- and post- treatment with Erenumab

Abstract: Background Migraine involves central and peripheral nervous system mechanisms. Erenumab, an anti-calcitonin gene-related peptide (CGRP) receptor monoclonal antibody with little central nervous system penetrance, is effective for migraine prevention. The objective of this study was to determine if response to erenumab is associated with alterations in brain functional connectivity and pain-induced brain activations. Methods Adults with 6–25 migraine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Recent MRI studies on resting-state functional connectivity and BOLD (i.e. blood-oxygen-level-dependent) measurements in response to moderately painful heat stimulation in patients treated with erenumab, showed that, in responders, there was a different response within the network elaborating pain stimuli (27). These studies are in favor of connectivity changes within the pain-related cortical areas, coherent with the therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent MRI studies on resting-state functional connectivity and BOLD (i.e. blood-oxygen-level-dependent) measurements in response to moderately painful heat stimulation in patients treated with erenumab, showed that, in responders, there was a different response within the network elaborating pain stimuli (27). These studies are in favor of connectivity changes within the pain-related cortical areas, coherent with the therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…four frequency bands that we considered: delta (0.5-3.5 Hz), theta (4-7 Hz), alpha (8-12 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Network Analysismentioning
confidence: 99%
“…The older age of the patients may suffer from the longer duration of migraine, together with CM and MOH, leading to changes in the brain's structure [ 18 , 19 ] and making it more difficult for the CGRP-mABs to be effective. In such cases, erenumab, which has been suggested to have the potential to improve the functional structure of the brain [ 20 ], maybe a better choice. It is also possible that those who were ineffective were already taking several medications, and they may have modified the CGRP-mABs effects.…”
Section: Discussionmentioning
confidence: 99%
“…The structural and functional properties of graphs of brain networks can be quantitatively investigated through measures of [ 239 ]: Functional segregation, e.g., clustering coefficients [ 248 , 249 , 250 , 251 , 252 ] and modularity [ 253 ]. Functional integration, based on the concept of path [ 248 , 254 ] and estimating the ease of communication between brain areas.…”
Section: Functional Connectivity Estimation Approachesmentioning
confidence: 99%
“…Functional segregation, e.g., clustering coefficients [ 248 , 249 , 250 , 251 , 252 ] and modularity [ 253 ].…”
Section: Functional Connectivity Estimation Approachesmentioning
confidence: 99%